(untitled) (GAIMS Journal of Medical Sciences, 2023)
Immune thrombocytopenic purpura (ITP) is a condition where the body’s immune system mistakenly attacks and destroys platelets, resulting in a decreased platelet count. This leads to the development of purpura on the skin and may cause bleeding episodes due to the presence of antibodies that target and damage platelets. Excluding the usual suspects helps in identifying the underlying causes of thrombocytopenia. The diagnosis of immune thrombocytopenia (ITP) relies on clinical suspicion and the presence of thrombocytopenia, as indicated on a normal peripheral smear. Bone marrow examination is performed in order to eliminate the possibility of leukemia, myelodysplastic syndrome or aplastic anemia. Circulating platelets become sensitized due to the presence of IgG autoantibodies. As a result, these cells are swiftly eliminated by antigen-presenting cells, such as macrophages, which are primarily found in the spleen, and occasionally in the liver or other parts of the monocyte-macrophage system. In response, the bone marrow increases the production of platelets. ITP frequently occurs in healthy individuals, including children and young adults, following a viral infection. Certain medications can also lead to immune thrombocytopenia, which is practically indistinguishable from idiopathic thrombocytopenic purpura. Children usually recover spontaneously within a few weeks or months, and splenectomy is rarely required. However, spontaneous remissions necessitating splenectomy in young adults are uncommon in the first several months following diagnosis. This article discusses the most frequent causes of ITP and outline an interdisciplinary diagnostic and therapeutic approach based on current research.